The New Direction of Indonesian Character Education: Bullying, Moral Decadence, and Juvenile Delinquency - AB. Musyafa Fathoni; Mubaidi Sulaeman; Elima Amiroh Nur Azizah; Yuslia Styawati; Mahendra Utama Cahya Ramadhan (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
Purpose – This article aims to provide a new direction for Character Education in minimizing bullying and preventing moral decadence and delinquency in adolescents in the school environment with a Prophetic Parenting approach. Design/methods/approach – This research used a qualitative method of literature type by collecting literature and data from books, scientific journal articles, yellow books, and Indonesian laws and regulations to reconstruct Character Education in Indonesia that has not been effective in responding to bullying, moral decadency, and juvenile delinquency, using the Prophetic Parenting approach. Findings – The first thing that the Prophet strongly emphasized in Character Education was a prophetic character, which includes qualities such as siddiq, amanah, tabligh, and fatimah. Second, in character building, following the teachings of the Prophet Muhammad, is important to prioritize the language of deeds rather than words alone. Third, the Prophet Muhammad’s approach taught strong moral and ethical principles. Parents can refer to verses in the Qur'an that emphasize the importance of behaving well, avoiding humility, and humiliating others. Fourth, parents should encourage children to be open about their experiences at school. Fifth, in overall efforts to overcome juvenile delinquency, the Prophetic Parenting approach can be a guide in shaping the character of adolescents with Islamic values and ethics. Research implications/limitations – The research has theoretical implications that, to minimize the occurrence of bullying, moral decency, and juvenile delinquency, it is necessary to apply parenting that refers to the concept of the Prophet SAW in building the character of Indonesian children toward a golden Indonesia in 2045. Originality/value – The research provides direction for incorporating the Prophetic Parenting approach into the Indonesian education curriculum in Indonesia to build Character Education that involves the family environment.